Strategic Thinking as a Crial Factor of Business Competitiveness (Revista LIDER, 2020)
The aim of this paper is to analyze how the answers to the questions of strategic thinking can be a critical factor in business competitiveness and contribute to its success. We consider the theory based on industry and resource-based theory. The main question is how one can maintain the strategic mindset when evaluating the objectives and resources of the company with respect to the forces governing competition? The method used was to build an analytical relationship between strategic thinking and competitive forces allowing the design of strategies that consider internal resources whose execution also contribute or effect positively its profitability.